2006
DOI: 10.1111/j.1365-2435.2006.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Root strength and trampling tolerance in the grass Paspalum dilatatum and the dicot Lotus glaber in flooded soil

Abstract: Summary 1.We studied the differences in root strength of species with contrasting root structural types (the grass Paspalum dilatatum and the dicot Lotus glaber ), and their relationship with tolerance to simulated cattle trampling under flooding conditions. 2. Root strength was analysed through measurement of the pressure required to cause root collapse. The responses of aerenchyma and plant mass to flooding and trampling were studied. 3. Root aerenchyma increased from 28·0 to 40·2% in P. dilatatum and from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
(51 reference statements)
6
38
0
2
Order By: Relevance
“…In our work, the plants remained in the recovery period for 5 weeks, trying to emulate a field situation in which the forage resource can then be grazed without being detrimental to the survival of the plants. It has been demonstrated that L. tenuis plants with a high proportion of aerenchymatous tissue are severely affected during a post‐flooding‐early grazing due to roots collapse by cattle trampling (Striker, Insausti, Grimoldi, & Leon, ). Our results showed that Lt and LtxLc, which presented the best response under flooding, also performed best during the recovery period (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In our work, the plants remained in the recovery period for 5 weeks, trying to emulate a field situation in which the forage resource can then be grazed without being detrimental to the survival of the plants. It has been demonstrated that L. tenuis plants with a high proportion of aerenchymatous tissue are severely affected during a post‐flooding‐early grazing due to roots collapse by cattle trampling (Striker, Insausti, Grimoldi, & Leon, ). Our results showed that Lt and LtxLc, which presented the best response under flooding, also performed best during the recovery period (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions, plants are typically exposed to multiple stress factors (Striker et al . ; Valladares et al . ; Anten et al .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, flooding rapidly reverts the grazing effects on the plant community by promoting the abundance of flood‐tolerant graminoids and reducing the presence of weed forbs (Insausti et al 1999), most of which are flood‐sensitive species (Grimoldi et al 2005). The legume L. tenuis also persists because of its higher flooding tolerance under conditions that do not involve trampling (Striker et al 2005, 2006). Recently, we identified the grass Paspalum dilatatum as tolerant and some coexisting dicot species (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identified the grass Paspalum dilatatum as tolerant and some coexisting dicot species (i.e. weed forbs and the legume L. tenuis ) as sensitive to the combination of flooding and trampling (Striker et al 2006, 2007). We demonstrated that the generation of aerenchyma tissue induced by flooding increases the root weakness of the forb species but has no effect on the strength of graminoid roots (Striker et al 2006, 2007).…”
Section: Introductionmentioning
confidence: 99%